Cone photoreceptor phosphodiesterase PDE6H inhibition regulates cancer cell growth and metabolism, replicating the dark retina response - Ceren Yalaz; Esther Bridges; Nasullah K. Alham; Christos E. Zois; Jianzhou Chen; Karim Bensaad; Ana Miar; Elisabete Pires; Ruth J. Muschel; James S. O. McCullagh; Adrian L. Harris (Cancer & Metabolism)
Abstract Background PDE6H encodes PDE6γ′, the inhibitory subunit of the cGMP-specific phosphodiesterase 6 in cone photoreceptors. Inhibition of PDE6, which has been widely studied for its role in light transduction, increases cGMP levels. The purpose of this study is to characterise the role of PDE6H in cancer cell growth. Methods From an siRNA screen for 487 genes involved in metabolism, PDE6H was identified as a controller of cell cycle progression in HCT116 cells. Role of PDE6H in cancer cell growth and metabolism was studied through the effects of its depletion on levels of cell cycle controllers, mTOR effectors, metabolite levels, and metabolic energy assays. Effect of PDE6H deletion on tumour growth was also studied in a xenograft model. Results PDE6H knockout resulted in an increase of intracellular cGMP levels, as well as changes to the levels of nucleotides and key energy metabolism intermediates. PDE6H knockdown induced G1 cell cycle arrest and cell death and reduced mTORC1 signalling in cancer cell lines. Both knockdown and knockout of PDE6H resulted in the suppression of mitochondrial function. HCT116 xenografts revealed that PDE6H deletion, as well as treatment with the PDE5/6 inhibitor sildenafil, slowed down tumour growth and improved survival, while sildenafil treatment did not have an additive effect on slowing the growth of PDE6γ′-deficient tumours. Conclusions Our results indicate that the changes in cGMP and purine pools, as well as mitochondrial function which is observed upon PDE6γ′ depletion, are independent of the PKG pathway. We show that in HCT116, PDE6H deletion replicates many effects of the dark retina response and identify PDE6H as a new target in preventing cancer cell proliferation and tumour growth.